2019
DOI: 10.1016/j.jds.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Ozone application as adjunctive therapy in chronic periodontitis: Clinical, microbiological and biochemical aspects

Abstract: Background/purpose The application of ozone as an adjunctive treatment represents a new approach in the management of chronic periodontitis. The purpose of this study was to evaluate the clinical, biochemical and microbiological efficacy of ozone treatment as an adjunct to scaling and root planing (SRP) in generalized chronic periodontitis (GCP) patients. Materials and methods Eighteen patients (9 males and 9 females; aged from 28 to 47 years, mean age of 40 ± 6.51 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 46 publications
2
22
0
1
Order By: Relevance
“…Our results are in accordance with a previous study conducted by Skurska et al [39], which demonstrated a significant decrease in periodontal inflammatory indices after the association of periodontal treatment and gaseous ozone compared to the control group. In contrast, Uraz et al [40] conducted a similar study showing that clinical parameters in patients with periodontitis did not improve with the adjunct of ozone therapy to conventional periodontal treatment. The authors observed that were no significant differences between two treatments groups for any of the microbiological, clinical and biochemical parameters.…”
Section: Discussionmentioning
confidence: 96%
“…Our results are in accordance with a previous study conducted by Skurska et al [39], which demonstrated a significant decrease in periodontal inflammatory indices after the association of periodontal treatment and gaseous ozone compared to the control group. In contrast, Uraz et al [40] conducted a similar study showing that clinical parameters in patients with periodontitis did not improve with the adjunct of ozone therapy to conventional periodontal treatment. The authors observed that were no significant differences between two treatments groups for any of the microbiological, clinical and biochemical parameters.…”
Section: Discussionmentioning
confidence: 96%
“…For Pg , a TaqMan-based assay was performed, according to Uraz et al [ 64 ], to quantify Pg 16S rRNA, the gene encoding the small subunit of 16S ribosomal RNA. The TaqMan Gene Expression Custom Assay was provided by Life Technologies (Thermo Fisher Scientific) with the following primers: 5′-GCGCTCAACGTTCAGCC-3′ forward primer, 5′-CACGAATTCCGCCTGC-3′ reverse primer and probe FAM-CACTGAACTCAAGCCCGGCAGTTTCAA-TAMRA.…”
Section: Methodsmentioning
confidence: 99%
“…32 Nanomaterials like Bioactive glass, carbon nanomaterials, Titanium nanotubes covered dental inserts, nanoceramics for bone recovery; nanobiomaterial being utilized for the planning of platforms for recovery of periodontium; metallic nanoparticles as toothpaste and mouth flushes for control of oral biofilm and nanoparticles for neighborhood drug conveyance, Nanorobots for oral absense of pain, drug conveyance and so forth. 33 Examination is being done in the field of nanotechnology for delivering better and even adjusted items for periodontal recovery with the end of reactions and expanding the biocompatibility of the item. 34,35…”
Section: Nanotechnologymentioning
confidence: 99%